Regioselective Halogenation of Poly(lactide) by Free‐Radical Process1. Issue 2 (29th August 2013) - Beuille, Eric; Darcos, Vincent; Coudane, Jean; Lacroix‐Desmazes, Patrick; Nottelet, Benjamin; Kontopoulou, Marianna
<x xml:space="preserve">Abstract</x> Modification of the biodegradable and renewable poly(lactide) (PLA) to provide functional aliphatic polyesters is highly desirable to meet application requirements. In this context, the objective of this work is to evaluate the possibility of using free‐radical substitution as a simple and non‐degrading method to yield the desired functional PLA. Halogenation of PLA is carried out in solution and various reaction conditions are evaluated. Halogenated PLAs are characterized by 1H NMR spectroscopy and size exclusion chromatography (SEC) to evaluate the substitution ratios and to check the non‐degrading character of the radical modification. Furthermore, reactions on model compounds as well as MALDI‐TOF analyses are performed to elucidate the involved mechanism. The combined results prove the free‐radical halogenation of PLA in solution to be regioselective with only the ω‐halogenated PLA being obtained without main‐chain substitution.<inline-graphic xlink:href="ark:/27927/pgg4sprprx5" content-type="mren201300136-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />